PARP1 interacts with STAT3 and retains active phosphorylated-STAT3 in nucleus during pathological myocardial hypertrophy. (15th October 2018) - Wang, Luping; Li, Zhuoming; Tan, Yinzi; Li, Qian; Yang, Hanwei; Wang, Panxia; Lu, Jing; Liu, Peiqing
Abstract: The activation of signal transducer and activator of transcription 3 (STAT3) positively regulates myocardial hypertrophy, and its transcriptional activity is finely conditioned by diverse extracellular growth factors and cytokines. Here, we introduce novel evidence that poly(ADP-ribose) polymerase 1 (PARP1) interacts with STAT3 and promotes its activation in cardiomyocytes and rat heart tissues. PARP1 activity and phosphorylated STAT3 were augmented by hypertrophic stimuli both in vitro and in vivo . Infection of PARP1 adenovirus induced cardiomyocyte hypertrophy, which could be prevented by STAT3 knockdown or inhibition. Additionally, PARP1 enhanced STAT3 phosphorylation level, nuclear accumulation and transcriptional activity. Mechanistically, PARP1 interacts with STAT3 and retains active phosphorylated-STAT3 in nucleus. In conclusion, our findings provide the first evidence that PARP1 exacerbates cardiac hypertrophy by stabilizing active phosphorylated-STAT3, which suggests that multi-target therapeutic strategies counteracting PARP1 activity and STAT3 activation would be potential for treating cardiovascular diseases. Highlights: STAT3 participates in PARP1-induced cardiomyocyte hypertrophy. PARP1 retains active phosphorylated-STAT3 in nucleus. The interaction between PARP1 and STAT3 upregulates STAT3 transcriptional activity. The retention of p-STAT3 by PARP1 in nucleus is independent of JAK2 activation.